TWO REPORTS ON ETHNO MUSICOLOGICAL RESEARCH - FERARU, Tudor (Studia Universitatis Babes-Bolyai Musica, 2009)
The two reports attempt to clarify several terminological and classification issues related to the study of folk song. From an ethnomusicologist’s point of view, the concepts of composition, improvisation, authorship, paternity or similarity are not as clear-cut as might be generally understood. Several writings by prominent scholars Bruno Nettl, Alan P. Merriam and Stephen Erdely are used as a base for the debate over these concepts. The first report focuses on the problem of what exactly constitutes music and musical creation, a question that seems to receive distinct answers in different cultural contexts around the world. The second report presents and compares various methods of classification applied to folk tunes and tune families.